The regulation of video-sharing platforms and harmful content in Ireland and Europe. (1st November 2021) - Murphy, Kenneth
The current commentary will provide an overview of Ireland's proposed legislation for regulating video-sharing platform's (VSPs) user-generated content and the proposed Irish national regulatory framework that will oversee it. Many of the largest VSPs, such as YouTube, Facebook and Twitter, designated for regulation under the revised Audiovisual Media Services Directive (EU) 2018/1808 (AVMSD), base their European operations in the Republic of Ireland. Thus, based on the country of origin (CoO) principle, the Irish National Regulatory Authority (NRA) will regulate the harmful user-generated content, and commercial content of the largest VSPs and platforms with in which shared video is a significant feature. The commentary will also address the concerns raised by Ireland's political-economic model and the inferred light-touch regulation interpreted as an aspect of how the State competes for Foreign Direct Investment (FDI). A low corporate tax regime, well-educated English-speaking population and access to the European Union has made Ireland a favoured location for primarily US-based technology companies. Alongside these attractions is a recent history of market-conforming governance that has left Ireland open to criticism of trading light-touch regulation for FDI. Ireland's initial light-touch approach to Europe-wide data privacy regulation has been a case in point.